The Hymenoptera collections of William Edward Shuckard and the dispersal of his type material. - Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 1998)
An inquiry is made into the dispersal of the Hymenoptera collections formed by William Edward Shuckard and the survival of his type material.KeywordsT. Desvignes - W.H.L. Walcott - W.W. Saunders - E. Saunders - Hope Entomological Collections, Oxford - Natural History Museum, London - dispersal of some 19th Century entomological collections.